Soil bacterial community response to continuous cropping of cotton - Ma, Zheng; Li, Peng; Yang, Chuanzhen; Feng, Zili; Feng, Hongjie; Zhang, Yalin; Zhao, Lihong; Zhou, Jinglong; Zhu, Heqin; Wei, Feng (Frontiers in Microbiology, 2023)
Long-term continuous cropping can lead to the outbreak of soil-borne diseases and decline of annual crops yield. Overcoming the obstacles of continuous cropping is of great significance for the sustainable development of modern agriculture. Soil microbes are important for plant health, but the effects of continuous cropping on soil microbiome are still poorly understood. This study analyzed changes in soil bacterial community composition of Aksu (AKS) and Shihezi (SHZ) in Xinjiang Province during 1 to 20 years of continuous cropping by 16S amplicon sequencing. The results showed that the incidence of cotton Verticillium wilt increased with the continuous cropping years. The bacterial alpha diversity in the AKS soil increased with the increase of continuous cropping years, while that in the SHZ soil decreased. The results of beta diversity analysis showed that there were significant differences in soil bacterial communities between different continuous cropping years and between different soils. The results of community composition changes at the level of main phyla and genus showed that the relative abundance of Actinobacteria, Bacteroidetes and Streptomyces decreased with the increase of continuous cropping years in the AKS and the SHZ soils. In addition, Actinobacteria, Propionibacteriales and Nocardioidaceae were significantly enriched at the early stage of continuous cropping. Network analysis showed that long-term (≥8 years) continuous cropping interfered with the complexity of soil bacterial co-occurrence networks and reduced collaboration between OTUs. These findings suggested that continuous cropping and soil origin jointly affected the diversity and structural composition of bacterial communities, and the loss of Actinobacteria might be one of the causes for continuous cropping obstacles.